2018
DOI: 10.12659/msm.907783
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Indocyanine Green Plasma Disappearance Rate on Liver Function and Complications After Liver Transplantation

Abstract: BackgroundThe aim of this study was to investigate the correlation between indocyanine green plasma disappearance rate (ICG-PDR) and allograft function as well as postoperative complications after liver transplantation.Material/MethodsIn this prospective study, 115 cases of adult liver transplantation performed from 1 June 2016 to 1 December 2016 were enrolled. These 115 patients were divided into a group of PDR <18%/min (50 cases) and a group of PDR ≥18%/min (65 cases). The rates of liver recovery, postoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 30 publications
0
4
0
7
Order By: Relevance
“…Additionally, they found that with a normal value of ICG-PDR, angiography was unnecessary in emergency situations, suggesting that ICG-PDR may be more sensitive than angiography (62). Sun et al also investigated ICG-PDR in 115 LT patients, and found that hepatic arterial complications and rates of pneumonia were higher in the ICG-PDR <18%/minute group compared to a control (63). Collectively, these studies show that the ICG clearance rate can provide a reliable, convenient, and low-cost postoperative test to predict mortality and surgical complications.…”
Section: Predicting Early Mortality and Complications By Icg Clearance Ratementioning
confidence: 99%
“…Additionally, they found that with a normal value of ICG-PDR, angiography was unnecessary in emergency situations, suggesting that ICG-PDR may be more sensitive than angiography (62). Sun et al also investigated ICG-PDR in 115 LT patients, and found that hepatic arterial complications and rates of pneumonia were higher in the ICG-PDR <18%/minute group compared to a control (63). Collectively, these studies show that the ICG clearance rate can provide a reliable, convenient, and low-cost postoperative test to predict mortality and surgical complications.…”
Section: Predicting Early Mortality and Complications By Icg Clearance Ratementioning
confidence: 99%
“…Its removal from the blood depends on the hepatic blood flow, parenchymal cell function, and biliary excretion. It is expressed as half-life time, blood clearance, or plasma disappearance rate (ICG-PDR) smaller than 15% associated with a higher rate of primary dysfunction [50]. The bedside ultrasound imaging methods with hepatic blood vessel Doppler examination are usually performed on the day of surgery or on the first postoperative one in order to evaluate the patency of the hepatic artery, the portal vein, and the hepatic vein.…”
Section: Liver Allograft Functionmentioning
confidence: 99%
“…Diante do potencial risco para disfunção de órgãos provenientes de doadores cadavéricos, torna-se necessária a avaliação do enxerto com o intuito de predizer a incidência de complicações pós-operatórias nos seus respectivos receptores 58 .…”
Section: Disfunção Do Enxerto Hepáticounclassified
“…Por mais que haja escalas de pontuação para avaliação hepática como Child-Pugh e MELD, com a finalidade de diagnosticar hepatopatias avançadas e priorizá-las de acordo com a gravidade dos receptores antes do transplante, falta sensibilidade e especificidade para ambas no contexto pósoperatório, sem aplicação prática no caso de avaliação da função do enxerto 58 .…”
Section: Disfunção Do Enxerto Hepáticounclassified
See 1 more Smart Citation